The Effect of Principal’s Competence and Community Participation on the Quality of Educational Services - Zulaiha, Deni; Lian, Bukman; Mulyadi, Mulyadi (Journal of Social Work and Science Education, 2020)
This research was conducted at Public Elementary School 68 Palembang with 34 teachers as respondents in the study sample. In this study there are three research variables consisting of two independent variables Principal Competence (X1) and Community Participation (X2), and one dependent variable Quality of Educational Services (Y). The extent to which the realization and role of community participation in education depends on the understanding of the community itself in education, and depends on the ability of the school. Quality education services are educational services that are in accordance with the plan and achieve the goals set and can meet the expectations and needs of customers. The results obtained in this study illustrate that the quality of educational services in Public Elementary School 68 Palembang is very good and can meet customer needs.